Análise da evolução do CAR e da cobertura da terra na zona do Rio Tauá, 2011-2021, Santo Antônio do Tauá (PA) - VIEGAS, Josimar Antônio Silva (2022)
The Forest Code published on May 25th, 2012 established norms for the preservation of native vegetation in the Brazilian territory bringing with it new monitoring and inspection methods and the Rural Environmental Registry (CAR) was created to gather information from rural properties and possessions in an electronic platform, promoting a national database to expand environmental inspection. This study aims to analyze the Rural Environmental Registry of Pará (CAR/PA) in an period of ten years in 2011 and 2021 using geoprocessing tools in the Rio Tauá Zone, located in the municipality of Santo Antônio do Tauá/PA. Based on the specific objectives it is intended to make a number diagnosis of registrations carried out until the year 2021, classifying them according to their status in the Rural Environmental Registration System of Pará (SICAR/PA), demonstrating the type of rural property considering the Agrarian Reform Law, in addition to classifying land use and land cover to identify environmental information on rural properties or possessions such as remnants of native vegetation, Permanent Preservation Areas (APPs), Consolidated Areas, Legal Reserve Areas (ARLs) , environmental easement areas and unconsolidated areas. To carry out this analysis, cartographic databases referring to rural properties in the municipality were arranged, acquired from the State Secretary for the Environment and Sustainability (SEMAS/PA) in partnership with the Technical Assistance and Rural Extension Company of Pará (EMATER/PA). Using the Geographic Information Systems in open source software, the bases were compared to the images of the collection 6 of annual maps on land use and cover from MapBiomas project, mosaics from the Landsat satellite series from 2010 and 2020 to identify suppression or the spread of native vegetation in rural properties with CAR. The predominant presence of properties in an active status in SICAR/PA was verified in addition to the prevalence of smallholdings, that are rural properties with less than one fiscal module. It was observed that there was suppression of native vegetation in the study area, presenting in 2020 51.63% of the preserved area, while in 2010 they were 54.78%. In the same way, there was growth in pasture areas, which in 2010 occurred from 42.38% to 43.99% in 2020.